Clinical, histopathological, and immunological evaluation of a series of patients with erythema nodosum. (24th February 2016) - De Simone, Clara; Caldarola, Giacomo; Scaldaferri, Franco; Petito, Valentina; Perino, Francesca; Arena, Vincenzo; Papini, Manuela; Caproni, Marzia; Peris, Ketty
Abstract: Background: The pathogenesis of erythema nodosum (EN) is still poorly understood, and studies evaluating the involvement of a cytokine network are very scarce. Objectives: To investigate clinical and pathological features, the cytokine profiles, and the balance of T‐regulatory (Treg) and T‐helper (Th)17 cells in serum and lesional skin of patients with EN. Methods: Patients with a diagnosis of EN were consecutively enrolled, and their clinical and histopathological features were recorded. A panel of cytokines was evaluated in both serum and lesional skin using enzyme‐linked immunosorbent assay. Real‐time polymerase chain reaction was performed to evaluate the Treg/Th17 cell balance. Results: Histopathological examination of skin biopsy specimens from all patients (four women and one man) showed classical features of EN. The most widely expressed cytokines were innate immunity cytokines (mainly tumor necrosis factor alpha, interleukin‐8 and ‐6) and growth factors (mainly granulocyte colony‐stimulating factor and monocyte chemoattractant protein‐1). The Treg/Th17 balance was highly different between patients. Conclusions: The present study emphasizes the crucial role of neutrophils in the pathogenesis of EN, as high levels of cytokines and growth factors mainly involved in neutrophil recruitment and activation were detected.